Perceptions and Misperceptions of Early Palliative Care Interventions for Patients With Hematologic Malignancies Undergoing Bone Marrow Transplantation - Suthumphong, Corey (Cureus, 2021)
Hematopoietic stem cell or bone marrow transplantation (BMT) is one of the most promising and potentially curative therapeutic options available for eligible patients with hematologic malignancies (HMs) or leukemias. However, the nature and clinical course of HMs, specifically for patients undergoing BMT, are associated with significant morbidity, symptomatology, healthcare service utilization, psychosocial and end of life issues, and overall decreased quality of life. Early palliative care (PC) consultations and utilization for patients with HMs have been shown to improve patient outcomes, satisfaction, and autonomy as well as caregiver burden, shared-decision making, and holistic care management. Despite the complexity of care and complications for patients with HM undergoing BMT, early PC interventions are systematically underutilized and understudied in this population compared to patients with solid tumors or non-HMs. Herein, the authors reviewed the current literature and knowledge to assess and report the perceptions and barriers to early PC utilization in the care of patients with HMs undergoing BMT. Clinical and cultural aspects of PC perceptions as well as current PC care models and potential directions for PC implementation were reviewed to inform future research studies and clinical practice guidelines necessary for the improvement of care and quality of life for HM patients undergoing BMT.